The development of English learning animation video using Melayu Bangka language - Tri Arie Bowo; Donal Fernado Lubis (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to produce an animation video with the main goal of helping elementary school children to understand English learning material, especially in the Covid-19 pandemic situation, which requires online learning. The novelty in this research is the making of English-learning animation videos using Melayu Bangka as the language of instruction. This study uses the Research & Development method with the Borg & Gall research steps, namely Potential and Problems, Data Collection, Product Design, Product Revision, Product Trial, Design Revision, Design Validation, Trial Usage, Product Revision, and Implementation. This research produced a learning video with nine sequences. Sequence 1 contains the opening, sequence 2 contains an introduction from Dini and Philip, sequence 3 contains songs sung by Philip and imitated by Dini, sequence 4 contains 'Recitation,' sequence 5 is a practice question, sequence 6 Dini fills in the blank spaces that Philip has given her, sequence 7 contains 'Sentence Formation,' sequence eight contains closing, and sequence 9 contains credit titles. This learning video goes through the Effectiveness Test with the results; namely Paired Samples Test showed that Sig. (2-tailed) of 0,000 < 0,05, which explained that there is an improvement between the results of learning English using video in the Pre-Test and Post-Test results. Independent Samples Test result showed Sig. (2 tailed) 0,011 < 0,05, which explained that English learning animation video using the Melayu Bangka language as the instruction could increase students learning outcomes. Similar research can be further developed related to learning English using regional languages as the language of instruction.